(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article investigates the role of digital tools in developing students’ speaking skills in English language classes. In modern language education, speaking competence is considered one of the most important indicators of communicative proficiency. However, many students still face difficulties in expressing their ideas fluently, confidently, and accurately in English. These difficulties are often connected with limited classroom time, fear of making mistakes, insufficient exposure to authentic speech, and lack of interactive practice. Digital tools such as language learning applications, online discussion platforms, video conferencing programs, voice recording tools, podcasts, and artificial intelligence-based speaking assistants can create additional opportunities for learners to practice oral communication beyond traditional classroom boundaries. The aim of the article is to analyze how digital tools support the development of fluency, pronunciation, vocabulary use, listening-response ability, and communicative confidence. The study is based on descriptive, analytical, and comparative methods. The article argues that digital tools are effective only when they are integrated into lessons with clear pedagogical objectives. If digital technologies are used without methodological planning, they may become distracting rather than productive. The findings show that digital tools increase students’ motivation, provide repeated speaking practice, support autonomous learning, and help teachers organize more student-centered lessons. At the same time, the article emphasizes several risks, including unequal access to technology, superficial use of applications, overdependence on automatic correction, and insufficient teacher control. The article concludes that digital tools should not replace the teacher but should function as supportive instruments for developing communicative competence.